Ta có : 17 chia hết cho ( 2a + 3 )
=> \(2a+3\inƯ_{17}\)
=> \(2a+3\in\left\{1;-1;17;-17\right\}\)
=> \(2a\in\left\{-2;-4;14;-20\right\}\)
=> \(a\in\left\{-1;-2;7;-10\right\}\)
Vậy \(a=\left\{-1;-2;7;-10\right\}\)
Vì 17 ⋮ 2a + 3
Nên 2a + 3 ∈ Ư(17) = {-1; 1; -17; 17}
Ta có bảng sau :
2a + 3 | -1 | 1 | -17 | 17 |
2a | -4 | -2 | -20 | 14 |
a | -2 | -1 | -10 | 7 |
➤ Vậy a ∈ {-10; -2; -1; 7}
Vì 17 ⋮ 2a + 3
Nên 2a + 3 ∈ Ư(17) = {-1; 1; -17; 17}
Ta có bảng sau :
2a + 3 | -1 | 1 | -17 | 17 |
2a | -4 | -2 | -20 | 14 |
a | -2 | -1 | -10 | 7 |
➤ Vậy a ∈ {-10; -2; -1; 7}